AB0500 B-Cell Depleting Therapy for SLE Related Refractory Thrombocytopenia. (10th June 2014) - Kim, Y.J.; Lee, E.-J.; Hong, S.; Koo, B.S.; Seo, W.J.; Oh, J.; Kim, Y.-G.; Lee, C.-K.; Yoo, B.
Abstract : Background: Autoimmune thrombocytopenia is a common manifestation of systemic lupus erythematosus (SLE) which may accompany bleeding risk and complications. B cell depleting therapy has been tried experimentally in SLE related thrombocytopenia refractory to standard treatment including corticosteroids, intravenous immunoglobulin, cyclophosphamide, and mycophenolate mofetil. Objectives: Here, we evaluated the efficacy of rituximab in SLE patients with severe thrombocytopenia refractory to conventional treatment. Methods: In our retrospective study, rituximab was administered in 5 patients with severe thrombocytopenia (platelet count <50 x10 9 /l) refractory to traditional treatments. Patients received i.v. rituximab at a dose of 500mg every week for 4 doses or 1000mg every 2 weeks for two doses. Peripheral CD 19 + B cell counts were evaluated before and after rituximab infusion. Results: Among five patients with refractory thrombocytopenia, 2/5 (40%) patients achieved complete responses (CR, platelet count >100 x10 9 /l) at week 4 after rituximab infusion. The CR rate increased to 3/5 patients at week 12, and 5/5 at week 24. Overall response (OR, platelet count >50 x10 9 /l) was achieved in 4/5 and 5/5 at week 4 and 12 respectively. Baseline B cell count was 158±133 x10 6 /l (range 3-348 x10 6 /l) and complete depletion (<5 x10 6 /l) was achieved in all 5 patients at week 4. Although 4 patients maintained normal platelet counts through 28 (range 11-48) months follow up period, one patient had relapsed 2 years after the last rituximab infusion with increasing B cell counts. However, good response was observed after reinfusion with rituximab. Conclusions: Our study showed that rituximab therapy induces a rapid and sustained remission in severe and refractory autoimmune thrombocytopenia in SLE patients. References: Pinto LF, Velasquez CJ, Prieto C et al. Rituximab induces a rapid and sustained remission in Colombian patients with severe and refractory systemic lupus erythematosus. Lupus 2011;20:1219-26. Lee JW, Kim HA, Sung JM et al. Successful treatment of refractory immune thrombocytopenia with anti-CD20 antibody in a patient with systemic lupus erythematosus. Lupus 2010;19:227-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3221